Novel high-efficiency visible-light responsive Ag4(GeO4) photocatalyst. Issue 11 (11th May 2017) - Zhu, Xianglin; Wang, Peng; Li, Mengmeng; Zhang, Qianqian; Rozhkova, Elena A.; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Wang, Zeyan; Huang, Baibiao
Abstract : The existence of an internal electric field promotes the separation of generated carriers and enhances the photocatalytic activity of polar materials. Abstract : A novel high-efficiency visible-light responsive Ag4 (GeO4 ) photocatalyst was prepared by a facile hydrothermal method. The photocatalytic activity of as-prepared Ag4 (GeO4 ) was evaluated by photodegradation of methylene blue (MB) dye and water splitting experiments. The photodegradation efficiency and oxygen production efficiency of Ag4 (GeO4 ) were detected to be 2.9 and 1.9 times higher than those of Ag2 O. UV-vis diffuse reflectance spectroscopy (DRS), photoluminescence experiment and photoelectric effect experiments prove that the good light response and high carrier separation efficiency facilitated by the internal electric field are the main reasons for Ag4 (GeO4 )'s excellent catalytic activity. Radical-trapping experiments reveal that the photogenerated holes are the main active species. First-principles theoretical calculations provide more insight into understanding the photocatalytic mechanism of the Ag4 (GeO4 ) catalyst.